An alternating experimental study on the combined effect of freeze-thaw and chloride penetration in concrete. (20th August 2020) - Sun, L.-Fang; Jiang, Kainian; Zhu, Xingji; Xu, Longjun
Highlights: An alternating test of chloride immersion diffusion and freeze-thaw was carried out. The test process is more in line with the actual situation of high latitudes. Total amount of chloride transport is larger than diffusion amount. Boundary concentration of chloride increases with the freeze-thaw cycles. Phase transition of pore solution can also drive the migration of chloride ions. Abstract: For the reinforced concrete structure in high latitude marine environment, the influence of freeze-thaw on chloride ion transport has been paid more and more attention. This paper intends to explore whether there is any other unknown coupling mode, by an alternating experiment of rapid freeze-thaw and chloride diffusion. For the purpose of data comparison, the tests of pure immersion diffusion are also carried out. It is found that the transport rate of chloride ions in the alternating test is significantly higher than that in the control groups; and the boundary concentration increases with the number of freeze-thaw cycles. The result indicates that there exists another influence mechanism of freeze-thaw on the transport of chloride ions, in addition to increasing the diffusion coefficient. Then, a new hypothesis mode is proposed and its mechanism is explained from the micro scale, i.e. the phase transition of pore solution during the freeze-thaw process can drive the migration of chloride ions dissolved in it.